Women’s Managerial Level Involvement in Tourism Sector in Pokhara - Paudel, Deepak Raj; Malla, Tek Bahadur (Journal of Nepalese Business Studies, 2012)
This study examines the factors that have effect on women’s managerial level involvement in hospitality sector of tourism industry in Lakeside, Pokhara; a popular tourism area in Nepal using a census survey of 100 women. The schedule questionnaire and 10 key informants’ interview (KII) were employed in order to collect primary data and to triangulate the results. Significance tests have been performed to determine the association between women’s level of participation with all other possible variables using Chi-square test. Demographic factors such as age and marital status; socioeconomic factors like educational level, prior family involvement, condition of work enviournment, household headship, and social barriers have been identified as independent variables that might have effect on level of women’s participation. The findings revealed that women’s participation in managerial position is low (29%) comparing to the operative level (71%). All socioeconomic factors have significant influence on women’s levels of participation. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page :39-52 Uploaded date: July 7, 2012